Writers and teachers as agents of social change (Journal for Studies in Humanities and Social Sciences, 2015)
Despite idealistic intentions, teachers at all levels and in most subjects are often accused of fostering Western hegemony and linguistic imperialism. However, a unique writing project in the southern African country of Namibia demonstrates that teachers can become agents of social change. One part of this project is an anthology of writings by indigenous women about their struggles with HIV and AIDS. Because AIDS has become a pandemic, now afflicting more than 35 million people worldwide, this anthology from Namibia, produced by the Women’s Leadership Centre, provides both a local and global (or “glocal”) orientation to the problem. It demonstrates the value of English in promoting health and human rights issues and more generally of empowering marginalized populations. It is also a supreme example of auto-ethnography, an account of one’s own experiences as grounded in and reflecting a culture, which has become a cutting-edge form of qualitative research. This paper explains how this “grass roots” writing project works and how to replicate it and develop relevant curriculum in other settings. A Reading Guide and high school curriculum have already been created, providing authentic, contextualized, and culturally appropriate materials for consciousness-raising activities focusing on reader response to social concerns, as well as for a typical language lesson.